PERAN TENAGA BIDAN TERHADAP KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET TAMBAH DARAH (FE) DI UPT PUSKESMAS SELATBARU KABUPATEN BENGKALIS - Elmisya, Santi; Yanti, Rifa; Sari Tanberika, Fajar; Oktora Sri, Ary (Ensiklopedia of Journal, 2025)
: Anemia in pregnant women is also said to have the potential to be dangerous not only for the mother but also for the child she is carrying. The impact that will occur due to anemia is an increased risk of miscarriage, premature birth, low birth weight, abnormalities that occur in the fetus and can increase the number of maternal and fetal morbidity and deaths. The incidence of anemia in Indonesia is 21.7%, and 26.4% of them are in the group of pregnant women. The aim is to determine the role of midwives in the compliance of pregnant women in consuming blood supplement (Fe) tablets at the UPT Puskesmas Selatbaru, Bengkalis Regency. The research method is descriptive correlational with a cross sectional approach. The population in this study was 129 pregnant women who visited from January to August 2024 at the Selatbaru Community Health Center and the sample used an accidental sampling technique of 35 respondents.  This research instrument uses a questionnaire, data analysis techniques use the Chi Square test. The research results showed that the majority of midwives' roles were 18 respondents (51,4%). The majority of pregnant women are not compliant in consuming Fe tablets, namely 23 respondents (65,7%) The results of the Chi Square test were obtained (p-value=0.000), meaning that there is a relationship between the role of midwives and the compliance of pregnant women in consuming Blood Enhancing Tablets (Fe) in UPT Puskesmas Selatbaru Bengkalis Regency. It is recommended that health workers, especially at community health centers, continue to provide information either through individual counseling during home visits or group counseling during the implementation of posyandu and that the information received will bring a positive perception for increasing health promotion in the future and providing counseling to pregnant women about tablets. Fe, impacts and benefits of Fe tablets for pregnant womenKeywords: The Role of Midwives, Compliance, Consuming Blood Supplement Tablets (Fe)